2013
DOI: 10.1111/sms.12080
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal regulation of calcium‐/phosphate‐regulating hormones in cyclists during the Giro d'Italia 3‐week stage race

Abstract: Calcium and phosphate are essential for cell functions, and their serum concentrations result from the balance between intestinal absorption, bony storage, and urinary excretion. Fibroblast growth factor 23 (FGF23), expressed by osteocytes and osteoblasts, acts in the kidney, leading to hypophosphatemia and low 1,25-dihydroxycholecalciferol synthesis, but suppresses parathyroid function. The aim of this study was to explore the effects of a high-energy demanding cycling race on this bone-kidney-parathyroid axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 58 publications
3
30
0
Order By: Relevance
“…Therefore, in kidney tissue physical exercise did not induce any changes in mRNA expression levels of FGF23responsive genes and VDR. Figure 4 shows there were no significant differences in plasma c-term FGF23 (9). However, confounding factors in that study could be the high dietary intake as well as weight loss, suggesting the observed changes might be an effect of altered metabolic state rather than mechanical loading of bone cells.…”
Section: Fgf23 Protein Expression In Tibiaementioning
confidence: 66%
See 1 more Smart Citation
“…Therefore, in kidney tissue physical exercise did not induce any changes in mRNA expression levels of FGF23responsive genes and VDR. Figure 4 shows there were no significant differences in plasma c-term FGF23 (9). However, confounding factors in that study could be the high dietary intake as well as weight loss, suggesting the observed changes might be an effect of altered metabolic state rather than mechanical loading of bone cells.…”
Section: Fgf23 Protein Expression In Tibiaementioning
confidence: 66%
“…Moreover, it was suggested FGF23 might be a 'molecular mediator of the whole-body effects of exercise originating from bone' (7). Indeed, serum FGF23 increased after endurance exercise in rat and human (8,9), indicating a potential systemic effect of local mechano-response in bone; FGF23 is produced exclusively in bone but acts on the kidneys, where it decreases the reabsorption and increases excretion of phosphate and also suppress 1α -hydroxylase (CYP27b1), reducing its ability to activate vitamin D and subsequently impairing calcium absorption (10). To our knowledge, the direct effect of different training types on FGF23 expression within bone has not…”
Section: Introductionmentioning
confidence: 99%
“…There is a possibility that the increase in FGF23 expression is conceivably due to high phosphate intake in these athletes, and might has no correlation with the 3 weeks bicycle activity. 10 As mentioned earlier, FGF23 can be induced by hyperphosphatemia, high parathyroid hormone, or increased vitamin D. Therefore, further study is needed to elucidate the role of calcium and phosphate role in FGF23 expression level during exercise. Other studies conducted on mice also found increased FGF23 gene and protein expression in gastrocnemius and gluteus maxima muscles after 1 week of physical exercise.…”
Section: Figure 1 Fgf23 Mrna Expression In Heart Muscle After Physicamentioning
confidence: 94%
“…7 FGF23 is a hormone secreted by osteocytes that functions to regulate phosphate metabolism and vitamin D. 8 FGF23 gene expression can be found in bone, thymus, brain, skeletal muscle, spleen, and heart muscle. 9 Lombardi et al 10 examined the levels of FGF23 in bicycle athlete's blood at the Giro Championships in Italy for 3 weeks and found an increase of 50% on day 21. Previous research conducted by Li et al 7 also showed that physical exercise for 60 minutes and 1 week can increase the level of fibroblast growth factor 23 (FGF23) in mouse blood and that physical exercise for 1 week can increase the expression of FGF23 mRNA in the skeletal muscle of mice.…”
Section: Introductionmentioning
confidence: 99%
“…The body cells respond to vitamin D in its active form through its receptor called vitamin D receptor (VDR) [40]. Vitamin D can regulate important mechanisms of immunity and inflammation and to modulate cardiovascular and musculoskeletal systems [41]. Indeed, it was shown that calcitriol suppresses NF-κB activity in a VDR-dependent manner.…”
Section: Introductionmentioning
confidence: 99%